Upaya Peningkatan Kesadaran tentang Bahaya Merokok melalui Penyuluhan Kesehatan di Pangkalan Ojek Karanggedang - Aisah Prihatini; Meida Bintari; Tarisa Dewi; Wiar Sari (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: Smoking is a factor that can increase the risk of various diseases that can lead to death. Smoking is the activity of smoking cigarettes that is carried out by humans in everyday life and smoking has become part of the needs of some people who have a tendency towards smoking. According to WHO in 2016, Indonesia is ranked at the top as a country with the highest number of smokers in the world, namely 76.2%. The UI demography institute writes that the number of deaths caused by smoking in 2004 was 427,948 people. This shows that 1,172 people per day or around 22.5% of total deaths in Indonesia are caused by smoking. Objective: The purpose of this study was to determine the effectiveness of health education as a form of effort to increase awareness about the dangers and effects of smoking in the community around the Karanggedang motorcycle taxi base. Method: The method chosen is observational and non-formal, carried out without selecting and determining the characteristics of the participants. Using leaflets as the medium and containing lectures and questions and answers at the end of the event as a form of evaluation whether there were changes before and after counseling was carried out. Result: Based on the results of the initial and final evaluations after the presentation of the material there were significant changes, there was an increase in knowledge which had an impact on the participants' awareness of the dangers and habits of smoking. When the final evaluation is carried out, all participants can answer together the questions asked by the moderator. Conclusion: The conclusion of this health education activity is that the series of activities from start to finish went well, the participants actively asked and answered questions with the team so that interactive communication was established. This activity has a positive effect on efforts to increase public awareness of the dangers of smoking for health. There were significant changes before and after the extension. It is hoped that the implementation of this activity can be a reminder and make them aware of the importance of maintaining health by avoiding smoking.